Hubungan Tingkat Pengetahuan Ibu dengan Penanganan Kejadian Kejang Demam pada Anak Usia 6 Bulan-5 Tahun di Puskesmas Tanjung Uncang - Sarita Miguna; Malahayati Rusli Bintang; Sitti Srie Luthfia Rekozar (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Febrile seizures occur in 2-5% of children aged 6 months-5 years. Although the incidence of febrile seizures in childhood generally has a good prognosis and can resolve spontaneously, the occurrence of seizures is considered frightening for most mothers. Actions for handling and/or management of febrile seizures are certainly influenced by the behavior of mothers, one of which is based on knowledge. Methods: This research method is descriptive analysis with a cross sectional approach conducted at Tanjung Uncang Public Health Center in December 2021. Sampling technique is accidental sampling with the number of samples as much as 72 mothers. The results of the study were analyzed with chi square. Results: Results of this study in 72 respondents, obtained (90,3%) respondents with less knowledge, (69,5%) respondents with less behavior for the handling of febrile seizure. The results of the chi-square test bivariate analysis found a meaningful relationship between the level of knowledge and the handling of febrile seizure (p=0,000). Conclusion:Based on this research that there is a relationship between the mother's level of knowledge and the handling of febrile seizures in children aged 6 months-5 years at the Tanjung Uncang Health Center in 2021.